Ernest Hemingway - American Writers 1 : University of Minnesota Pamphlets on American Writers - Young, Philip, 1918-1991 (Book collections on Project MUSE., 1959)
Ernest Hemingway - American Writers 1 was first published in 1959. Minnesota Archive Editions uses digital technology to make long-unavailable books once again accessible, and are published unaltered from the original University of Minnesota Press editions.